IBNU KHALDUN: KAJIAN TOKOH SEJARAH DAN ILMU-ILMU SOSIAL - Samsinas, Samsinas (Institut Agama Islam Negeri (IAIN) Palu, 2009)
This paper deals with Ibn Khaldun and his theory of circle (cyclical theory). This theory is based on historical realities in nomadic societies and also urban societies which have their own social solidarity, organizational structure and civilization. From this fact, he is known as the first figure who construct scientifically the methodology of the history of human thought, so that history can be developed both as science and philosophy. Subsequently, Ibn Khaldunâs ideas become the seeds for the development of social sciences, including sociology and economics.Kata Kunci: Ibnu Khaldun, sejarah sosial, filsafat sejarah, ilmu-ilmu Â sosial